(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Goats fed on high-quality and valuable forage provides the production of high quality milk and dairy products. In organic farming improper and poor feeding during lactation period reduce milk yield and quality of products. The goal of our research was to ascertain the post impact of different feedstuffs (oat meal, wheat bran, sunflower cake, rapeseed cake) on goat milk productivity and quality indices. The trial was carried out in farm “Bērzi”, Talsi district in autumn period for 60 days totally; it is, after including of these feedstuffs in feed ration. Sunflower meal fed in summer period increased in autumn period the content of goat milk fat by 6.7%, as well as by 7.5% increased protein content and decreased sugar content in milk by 0.5% compare to control. Rapeseed meal fed in summer resulted in increased milk fat by 5.1 % and decreased protein and sugar content in goat milk by 2.1 % and 1.6 % respectively in autumn period compare to control. The essential post impact p less then 0.05 on milk protein shown wheat bran which increased protein content in goat milk by 19.5% compare to control.